Univariable and multivariable Mendelian randomization study identified the key role of gut microbiota in immunotherapeutic toxicity - Baike Liu; Zheran Liu; Tianxiang Jiang; Xiangshuai Gu; Xiaonan Yin; Zhaolun Cai; Xiaoqiao Zou; Lei Dai; Bo Zhang (European Journal of Medical Research, 2024)
Abstract Background In cancer patients receiving immune checkpoint inhibitors (ICIs), there is emerging evidence suggesting a correlation between gut microbiota and immune-related adverse events (irAEs). However, the exact roles of gut microbiota and the causal associations are yet to be clarified. Methods To investigate this, we first conducted a univariable bi-directional two-sample Mendelian randomization (MR) analysis. Instrumental variables (IVs) for gut microbiota were retrieved from the MiBioGen consortium (18,340 participants). GWAS summary data for irAEs were gathered from an ICIs-treated cohort with 1,751 cancer patients. Various MR analysis methods, including inverse variance weighted (IVW), MR PRESSO, maximum likelihood (ML), weighted median, weighted mode, and cML–MA–BIC, were used. Furthermore, multivariable MR (MVMR) analysis was performed to account for possible influencing instrumental variables. Results Our analysis identified fourteen gut bacterial taxa that were causally associated with irAEs. Notably, Lachnospiraceae was strongly associated with an increased risk of both high-grade and all-grade irAEs, even after accounting for the effect of BMI in the MVMR analysis. Akkermansia, Verrucomicrobiaceae, and Anaerostipes were found to exert protective roles in high-grade irAEs. However, Ruminiclostridium6, Coprococcus3, Collinsella, and Eubacterium (fissicatena group) were associated with a higher risk of developing high-grade irAEs. RuminococcaceaeUCG004, and DefluviitaleaceaeUCG011 were protective against all-grade irAEs, whereas Porphyromonadaceae, Roseburia, Eubacterium (brachy group), and Peptococcus were associated with an increased risk of all-grade irAEs. Conclusions Our analysis highlights a strong causal association between Lachnospiraceae and irAEs, along with some other gut microbial taxa. These findings provide potential modifiable targets for managing irAEs and warrant further investigation.